The Triplex Confinium. International Research Project: Objectives, Approaches and Methods - Roksandić, Drago (1998)
The author justifies the need for the Triplex Confinium international research project as a multinational, interdisciplinary and interregional project focused on the triple frontier area betweeen the Habsburg Monarchy, Ottoman Empire and the Venetian Republic in the Early Modern Period.
Projekt MZOS
ENG